The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1097/hjh.0b013e328341d117
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacogenetic analysis of determinants of hypertension and blood pressure response to angiotensin-converting enzyme inhibitor therapy in patients with vascular disease and healthy individuals

Abstract: This large genetic association study identified genetic determinants of hypertension in three cohorts of patients with vascular disease and healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…This does not necessarily mean that HCM patients will not benefit from the prescription of drugs blocking the RAAS system. 35 However, small studies showing a positive effect of RAAS inhibitors on progression of hypertrophy and fibrosis in HCM need confirmation. 36,37 Furthermore, our study was limited to five candidate polymorphisms and the role of other common genetic variants in explaining phenotypic variability among HCM patients, which may act in a mutation-specific way, merits investigation perhaps in future genome-wide association studies.…”
Section: Discussionmentioning
confidence: 99%
“…This does not necessarily mean that HCM patients will not benefit from the prescription of drugs blocking the RAAS system. 35 However, small studies showing a positive effect of RAAS inhibitors on progression of hypertrophy and fibrosis in HCM need confirmation. 36,37 Furthermore, our study was limited to five candidate polymorphisms and the role of other common genetic variants in explaining phenotypic variability among HCM patients, which may act in a mutation-specific way, merits investigation perhaps in future genome-wide association studies.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation has been evaluated, usually by studying single nucleotide polymorphisms in RAAS genes in a retrospective manner in large clinical trials. 53,54 Emphasis has been on the ACE insertion/ deletion polymorphism. 55 Unfortunately, the effects were small and difficult to replicate, and, given the nonexistence of large prospective studies to further evaluate these findings, at this stage, there is no useful genetic information that can be applied to the individual patient to help choosing a specific RAAS blocker.…”
Section: Determinants Of Raas Blocker Response and The Degree Of Blocmentioning
confidence: 99%
“…Similar studies reported association of RAAS polymorphisms with response to ACEinhibitor therapy. 20,21 To our knowledge this is the first paper that describes the association between AGTR1 gene polymorphisms and hypertension in the Mexican population. The AGTR1 +573 C/T (rs5182) polymorphism was associated with the risk of developing hypertension in this population.…”
Section: Discussionmentioning
confidence: 99%